Explaining impossible and possible imaginings of pain - Paul Noordhof (Rivista Internazionale di Filosofia e Psicologia, 2021)
Jennifer Radden argues that it is impossible to imagine sensuously pain and explains this by noting that pains are sensory qualities for which there is no distinction between appearance and reality. By contrast, I argue that only basic sensuous imaginings of pain from the first person perspective are, with some qualifications, impossible. Non-basic sensuous imaginings of pain from the first person perspective are possible. I explain the extent to which imagining pain is impossible in terms of the conditions required for representing the painfulness of pain. I outline some difficulties with Radden’s favoured explanation and note how imagining pains may have a role in depression and, to that extent, keep open the option that it may have a partly delusional character.